2020
DOI: 10.5935/1518-0557.20190086
|View full text |Cite
|
Sign up to set email alerts
|

Three-parent babies: Mitochondrial replacement therapies

Abstract: The mitochondria are intracellular organelles, and just like the cell nucleus they have their own genome. They are extremely important for normal body functioning and are responsible for ATP production -the main energy source for the cell. Mitochondrial diseases are associated with mutations in mitochondrial DNA and are inherited exclusively from the mother. They can affect organs that depend on energy metabolism, such as skeletal muscles, the cardiac system, the central nervous system, the endocrine system, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
12
0
3
Order By: Relevance
“…PBT consists in the relocation of the PB1 or PB2, instead of the nuclear genetic material from the oocyte, to a healthy cytoplasm. 64 • PB1T: PB1 is isolated from the compromised MII oocyte and is relocated in the enucleated donor oocyte. This oocyte is subsequently fertilised with the partner sperm, which gives rise to a reconstituted zygote with healthy mtDNA, as well as the genetic material from the patient PB1 and sperm in the form of pronuclei.…”
Section: Heterologous Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…PBT consists in the relocation of the PB1 or PB2, instead of the nuclear genetic material from the oocyte, to a healthy cytoplasm. 64 • PB1T: PB1 is isolated from the compromised MII oocyte and is relocated in the enucleated donor oocyte. This oocyte is subsequently fertilised with the partner sperm, which gives rise to a reconstituted zygote with healthy mtDNA, as well as the genetic material from the patient PB1 and sperm in the form of pronuclei.…”
Section: Heterologous Approachmentioning
confidence: 99%
“…PBT consists in the relocation of the PB1 or PB2, instead of the nuclear genetic material from the oocyte, to a healthy cytoplasm. 64 …”
Section: Mitochondrial Replacement Techniques For Oocyte Rejuvenationmentioning
confidence: 99%
“…Algumas clínicas oferecem diagnóstico genético pré-implantacional (PGD) para medir o nível de heteroplasmia de mtDNA em embriões desenvolvidos in vitro. Essa conduta não é um padrão, pois devido ao padrão de multiplicação de mitocôndrias durante o desenvolvimento embrionário, o PGD não apresenta resultados confiáveis quanto à prevenção transmissão de mutação, uma vez que a taxa de mtDNA para um embrião se desenvolver sem manifestar a doença não é conhecido 10 .…”
Section: Técnicas De Substituição Mitocondrial Para Pacientes Com Síndrome De Leighunclassified
“…A notícia foi veiculada mundialmente pela mídia como o nascimento do bebê de três pais (Three-parent baby). Apesar de a técnica ter sido rapidamente aplicada na rotina clínica, podem ocorrer incompatibilidades entre os genomas mitocondrial e nuclear resultantes do processo e a técnica é recente e não bem discutido ainda 10 . Assim, este trabalho objetiva revisar os sinais e sintomas clássicos e as principais alterações moleculares da SL, bem como revisa as técnicas de transferência de DNA nuclear utilizadas em reprodução assistida que objetivam reduzir a chance de transmissão da SL e de outras síndromes causadas por mutações no mtDNA para os filhos de mães com a síndrome.…”
Section: Introductionunclassified
“…Mitochondria are important intracellular organelles responsible for energy production [ 9 ]. Previous studies have demonstrated that mitochondria perform an important role in cell death pathways [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%